SALMONELLA OSTEOMYELITIS OF THE LUMBAR SPINE: AN UNUSUAL PRESENTATION IN AN IMMUNOCOMPETENT MALE - Mohanty, Aroop; Pandita, Naveen; Kandwal, Pankaj; Omar, Balram Ji; Gupta, Pratima; Gupta, Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Prevalence of Salmonella vertebral osteomyelitis has increased in recent years due to greater number of spinal surgical procedures, ageing population, and intravenous drug abuse. It is a rare complication of Salmonella infection. We report a case of a 17-year-old male who presented with low back pain for past 1 month. Physical examination revealed spinal tenderness over L2-L5 spine with sensory and motor deficit. Magnetic resonance imaging of dorsolumbar spine showed spondylodiscitis at L2-L5 and epidural collection at L4-L5 level. The patient did not respond to conservative treatment and trial of antitubercular drugs. He underwent open discal biopsy and decompression laminotomy. Intraoperatively, he was found to have epidural abscess and discitis at L3-L4 level. Tissue and wound culture grew Salmonella typhi, and with antibiotic susceptibility guidance, he was treated with intravenous cefuroxime for 4 weeks. On his latest follow-up, there was complete recovery and fusion at diseased vertebrae level.